Transparency in United States healthcare sustainability: a scoping review - Sara Locke; Courtney Hadley; Jodi D Sherman; Andrew Hantel; Emily Senay (Environmental Research: Health, 2025)
The United States (U.S.) healthcare sector—a significant contributor to climate change through emissions, pollution, and waste—is beginning to integrate sustainability into operations. Sustainability science and accounting have been widely adopted across other industries to measure and communicate mitigation progress. Transparency, defined as ensuring accurate reporting and open disclosure of sustainability data, is critical. Without it, organizations risk ‘greenwashing,’ where misleading claims can erode public trust and undermine sustainability efforts. This scoping review evaluates the extent to which U.S. healthcare literature addresses transparency as a critical component of sustainability initiatives. This review identified peer-reviewed and non-peer-reviewed literature on environmental sustainability within U.S. healthcare from 1994 to 2024, with a focus on transparency and related concepts. Articles were excluded if they were not in English, corporate reports, advertisements, or irrelevant to U.S. healthcare sustainability. The following databases were searched: Ovid MEDLINE, Nexis Uni, Business Source Complete, Scopus, and Health Care Administration. Two independent reviewers screened and extracted the data, with a third resolving disagreements. Qualitative and thematic analyses were employed to assess if and how transparency was defined and operationalized in the context of healthcare sustainability. Of the 835 articles screened, 33 met inclusion criteria. Only 10 of the 33 articles both defined and operationalized transparency. Key focus areas included environmental sustainability practices in healthcare ( n = 18, 55%); ESG or CSR and public health impact ( n = 18, 55%); the business of healthcare ( n = 8, 24%); and policy-driven sustainability initiatives ( n = 7, 21%). Barriers included absence of mandates, standardization, and leadership. Despite a growing body of research on healthcare sustainability, studies addressing transparency are sparse. Limitations included a narrow keyword focus and limited databases searched. Transparent reporting could be considered the sixth ‘R’ in the 5 Rs of sustainability–refuse, reduce, reuse, recycle, repurpose, and report.